Documents of war: Understanding the Syrian conflict. Issue 2 (April 2015) - Price, Megan; Gohdes, Anita; Ball, Patrick
<x xml:space="preserve">Abstract</x> Researchers in Syria are doing their best to monitor the number of people killed in the ongoing conflict. A full and complete count is impossible amid the violence – but the extent to which killings can and cannot be documented reveals much about the nature of the fighting. By Megan Price, Anita Gohdes and Patrick Ball